2020
DOI: 10.1111/deci.12439
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Effect of Goal Misalignment and Metaknowledge Distribution on Team Decision Making in Operations and Supply Chain Management

Abstract: Many strategic decisions concerning firms’ operations and supply chain management (OSCM) are executed in teams of multiple functional specialists, to reap the proven benefits of internal integration. However, specialists bring with them not only diverse expertise, but also diverse goals and incentive structures. We examine how functional goal misalignment and the distribution of knowledge of who knows what (metaknowledge) affect self‐serving politics and the performance of cross‐functional teams. To test our m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 116 publications
(156 reference statements)
0
26
0
Order By: Relevance
“…If economic reward schemes are applied, the payments should reflect valid performance metrics like order picking performance (De Vries et al. , 2016) or supplier efficiency (Franke et al. , 2021), which is infeasible for our design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If economic reward schemes are applied, the payments should reflect valid performance metrics like order picking performance (De Vries et al. , 2016) or supplier efficiency (Franke et al. , 2021), which is infeasible for our design.…”
Section: Methodsmentioning
confidence: 99%
“…It avoids two fundamental problems: demand effects when participants try to cater to what they believe is the desired outcome of the study to maximize their compensation (Eckerd et al, 2020) and ethical problems of assigning lower payments per design. If economic reward schemes are applied, the payments should reflect valid performance metrics like order picking performance (De Vries et al, 2016) or supplier efficiency (Franke et al, 2021), which is infeasible for our design. Our study focuses on behavioral responses in line with the socialpsychology experimentation paradigm (Eckerd et al, 2020).…”
Section: Compensationmentioning
confidence: 99%
“…Such information is handy and accelerate the HSC performance Gupta et al ( 2019 ) and Paciarotti et al ( 2021 ) Information security It is defined as keeping people's privacy and avoid abusing such private information. Moreover, data encryption avoids data leakage for further misusing Patil et al ( 2021 ) and Gupta et al ( 2019 ) Technical skills It is referred to required skills for working with emerging technologies in order to make the most advantages of the technologies aiming at enhancing HSC performance Franke et al ( 2021 ), Kumar and Singh ( 2021 ) and Adesanya et al ( 2020 ) …”
Section: Methodsmentioning
confidence: 99%
“…The sourcing literature has shown that functional goal misalignment can trigger conflicts regarding the sourcing task and heated emotional debates that may tempt functions to influence the decision via politics, especially when some functions have superior knowledge levels (Franke and Foerstl 2020, Franke et al. 2021). However, formal work demands are not the sole determinant of individual behavior (Kanfer and Chen 2016).…”
Section: Literature Review and Theoretical Foundationsmentioning
confidence: 99%